The Relationship between Rumination and Emotional Self-Regulation with Attitudes Toward Addiction: The Mediating Role of Family Emotional Atmosphere - Gholam Reza Sheykhzadeh; Sajjad Basharpoor; Rogayeh Mohammadi; Reyhaneh Rad Kaftroudy (مطالعات روانشناختی, 2025)
The aim of this research was to examine the role of attitudes toward addiction based on rumination and emotional self-regulation, with the mediating effect of family emotional atmosphere in the city of Ardabil. This study was a descriptive-correlational research based on its nature and method. The statistical population included all high school students in Ardabil during the academic year 2023-2024. A total of 255 students were selected using cluster random sampling. Data were collected using questionnaires on attitudes toward addiction by Karimi, rumination by Nolen-Hoeksema and Morrow, emotional self-regulation by Tangney et al., and family emotional atmosphere by Byrne. The data were analyzed using Pearson correlation and structural equation modeling. The findings indicated that rumination had a significant positive direct effect on attitudes toward addiction, while emotional self-regulation and family emotional atmosphere had significant negative direct effects on attitudes toward addiction. The indirect effects showed that rumination and emotional self-regulation significantly had effect on attitudes toward addiction through the mediating role of family emotional atmosphere. Based on these findings, it is recommended to conduct workshops and training in schools to raise awareness about and address attitudes toward addiction.